Engineering electromagnetics and waves - Inan, Umran S.; Inan, Aziz S.; Said, Ryan K. (Always learning, 2016)
Electromagnetic Waves continues the applied approach used in the authors' successful Engineering Electromagnetics. The second book is appropriate for a second course in Electromagnetics that covers the topic of waves and the application of Maxwell's equations to electromagnetic events.